Antibody stability: A key to performance - Analysis, influences and improvement - Hui Ma (290168) (2020)
An antibody’s stability greatly influences its performance (i.e. its specificity and affinity). Thus, stability is a major issue for researchers and manufacturers, especially with the increasing use of antibodies in therapeutics, diagnostics and rapid analytical platforms. Here we review antibody stability under five headings: (i) measurement techniques; (ii) stability issues in expression and production (expression, proteolysis, aggregation); (iii) effects of antibody format and engineering on stability and (iv) formulation, drying and storage conditions. We consider more than 100 sources, including patents, and conclude with (v) recommendations to promote antibody stability. Other Information Published in: Biochimie License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.biochi.2020.08.019